Infection and the Kyoto Classification of Gastritis - Sun-Young Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Estimating the risk of Helicobacter pylori (H. pylori)-induced gastric cancer during endoscopic examination is important. Owing to recent advances in gastrointestinal endoscopy, the gross appearance of the background gastric mucosa has enabled discrimination of subjects with active, chronic, and past H. pylori infection from those with no history of infection. To provide subjective criteria for H. pylori infection-related endoscopic findings with increased risk of gastric cancer, the Kyoto classification of gastritis was proposed at the 85th annual meeting of the Japanese Society for Gastrointestinal Endoscopy in May 2013 in Kyoto. The main contents focus on determining the gastric cancer risk by scoring the endoscopic findings of the background gastric mucosa from 0 to 8. These important findings are not described in the Kyoto Global Consensus Conference proceedings published in English. To better estimate the gastric cancer risk during screening endoscopy in an H. pylori-prevalent population, knowledge of the Japanese version of the Kyoto classification is important. This new classification emphasizes the discrimination of subjects with H. pylori infection by assessing 19 endoscopic findings (presence of atrophy, intestinal metaplasia, diffuse redness, spotty redness, mucosal swelling, enlarged folds, sticky mucus, chicken skin-like nodularity, foveolar-hyperplastic polyp, xanthoma, depressed erosion, regular arrangement of collecting venules, fundic gland polyp, linear red streak, raised erosion, hematin deposit, multiple white and flat-elevated lesions, patchy redness, and map-like redness). In this review, the validity of the Kyoto classification is summarized in conjunction with several suggestions to resolve emerging H. pylori infection-related problems in Korea.